Remote ischemic preconditioning protects against spinal cord ischemia–reperfusion injury in mice by activating NMDAR/AMPK/PGC-1α/SIRT3 signaling - Changjiang Gu; Fanqi Kong; Junkai Zeng; Xiangwu Geng; Yanqing Sun; Xiongsheng Chen (Cell & Bioscience, 2023)
Abstract Background To study the protective effects of delayed remote ischemic preconditioning (RIPC) against spinal cord ischemia–reperfusion injury (SCIRI) in mice and determine whether SIRT3 is involved in this protection and portrayed its upstream regulatory mechanisms. Methods In vivo, WT or SIRT3 global knockout (KO) mice were exposed to right upper and lower limbs RIPC or sham ischemia. After 24 h, the abdominal aorta was clamped for 20 min, then re-perfused for 3 days. The motor function of mice, number of Nissl bodies, apoptotic rate of neurons, and related indexes of oxidative stress in the spinal cord were measured to evaluate for neuroprotective effects. The expression and correlation of SIRT3 and NMDAR were detected by WB and immunofluorescence. In vitro, primary neurons were exacted and OGD/R was performed to simulate SCIRI in vivo. Neuronal damage was assessed by observing neuron morphology, detecting LDH release ratio, and flow cytometry to analyze the apoptosis. MnSOD and CAT enzyme activities, GSH and ROS level were also measured to assess neuronal antioxidant capacity. NMDAR-AMPK-PGC-1α signaling was detected by WB to portray upstream regulatory mechanisms of RIPC regulating SIRT3. Results Compared to the SCIRI mice without RIPC, mice with RIPC displayed improved motor function recovery, a reduced neuronal loss, and enhanced antioxidant capacity. To the contrary, the KO mice did not exhibit any effect of RIPC-induced neuroprotection. Similar results were observed in vitro. Further analyses with spinal cord tissues or primary neurons detected enhanced MnSOD and CAT activities, as well as increased GSH level but decreased MDA or ROS production in the RIPC + I/R mice or NMDA + OGD/R neurons. However, these changes were completely inhibited by the absence of SIRT3. Additionally, NMDAR-AMPK-PGC-1α signaling was activated to upregulate SIRT3 levels, which is essential for RIPC-mediated neuroprotection. Conclusions RIPC enhances spinal cord ischemia tolerance in a SIRT3-dependent manner, and its induced elevated SIRT3 levels are mediated by the NMDAR-AMPK-PGC-1α signaling pathway. Combined therapy targeting SIRT3 is a promising direction for treating SCIRI.